Strategic Elevation of an Emerging Destination through a SWOT-Based Marketing Approach at Taman Jati Larangan - Bandiyah, Uswatun Nurul; Yosi Septa Mutiarni; Besti Ismi Riyanisma; Aisha Astriecia; Risky Setiawan (Journal of Language, Communication, and Tourism, 2025)
Taman Jati Larangan is a developing tourist destination with high cultural and historical potential. This study aims to formulate a strategic marketing plan through SWOT analysis, supported by the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. Employing a qualitative approach, data were collected via interviews, field observations, and document analysis. Key findings include strong internal assets such as community-led management, local wisdom-based attractions, and creative tourism innovation. Meanwhile, external opportunities such as mapped tourism routes and third-party investment potential present avenues for growth. The SWOT results place the site in the S-O (Strengths-Opportunities) quadrant, suggesting a Maxi-Maxi strategy. Recommended actions include developing agro-tourism based on green initiatives (e.g., catfish, farming), enhancing digital marketing, and creating integrated tourism packages. These findings provide both a strategic model and practical implications for stakeholder-driven rural tourism planning.